(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The present study was undertaken to evaluate the antipsychotic potential of Ocimum sanctum in experimental animal models. Male Wistar rats (180-220 g) and albino mice (25-30 g) were used for the study. The antipsychotic effect of the Ocimum sanctum was evaluated on haloperidol induced catalepsy, cooks pole climbing apparatus, locomotor activity on actophotometer, ketamine induced stereotype behavior. Different groups of rats were fed orally with a specially prepared diet containing various concentrations (2% w/w, 4% w/w and 8% w/w) of Ocimum sanctum leaves paste (OCLP) for 15 consecutive days. Further, the biochemical estimations were done by estimating brain dopamine levels. The OCLP produced significant dose dependent potentiation of haloperidol (1mg/kg, i.p.) induced catalepsy in rats, significantly increased the time taken by the rat to climb the pole in dose dependent manner, significantly decreased the locomotor activity. The OCLP significantly decreased ketamine (50 mg/kg, i.p.) induced stereotyped behavior in a dose dependent manner. Ocimum sanctum leaves paste (OCLP) significantly decreased the brain dopamine levels. The results suggest that OCLP posse’s antipsychotic activity. Further neurochemical investigation can explore the mechanism of action of the plant drug with respect to anti-dopaminergic functions and help to establish the plant as an antipsychotic agent.